Further delineation of the MECP2 duplication syndrome phenotype in 59 French male patients, with a particular focus on morphological and neurological features. Issue 6 (4th April 2018) - Miguet, Marguerite; Faivre, Laurence; Amiel, Jeanne; Nizon, Mathilde; Touraine, Renaud; Prieur, Fabienne; Pasquier, Laurent; Lefebvre, Mathilde; Thevenon, Julien; Dubourg, Christèle; Julia, Sophie; Sarret, Catherine; et al.
Abstract : The Xq28 duplication involving the MECP2 gene ( MECP2 duplication) has been mainly described in male patients with severe developmental delay (DD) associated with spasticity, stereotypic movements and recurrent infections. Nevertheless, only a few series have been published. We aimed to better describe the phenotype of this condition, with a focus on morphological and neurological features. Through a national collaborative study, we report a large French series of 59 affected males with interstitial MECP2 duplication. Most of the patients (93%) shared similar facial features, which evolved with age (midface hypoplasia, narrow and prominent nasal bridge, thick lower lip, large prominent ears), thick hair, livedo of the limbs, tapered fingers, small feet and vasomotor troubles. Early hypotonia and global DD were constant, with 21% of patients unable to walk. In patients able to stand, lower limbs weakness and spasticity led to a singular standing habitus: flexion of the knees, broad-based stance with pseudo-ataxic gait. Scoliosis was frequent (53%), such as divergent strabismus (76%) and hypermetropia (54%), stereotypic movements (89%), without obvious social withdrawal and decreased pain sensitivity (78%). Most of the patients did not develop expressive language, 35% saying few words. Epilepsy was frequent (59%), with a mean onset around 7.4 years of age, and often (62%) drug-resistant. Other medical issues were frequent: constipation (78%), and recurrent infections (89%), mainly lung. We delineate the clinical phenotype of MECP2 duplication syndrome in a large series of 59 males. Pulmonary hypertension appeared as a cause of early death in these patients, advocating its screening early in life.